2014
DOI: 10.1051/0004-6361/201424113
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic signatures of extratidal stars around the globular clusters NGC 6656 (M 22), NGC 3201, and NGC 1851 from RAVE

Abstract: Context. Stellar population studies of globular clusters have suggested that the brightest clusters in the Galaxy might actually be the remnant nuclei of dwarf spheroidal galaxies. If the present Galactic globular clusters formed within larger stellar systems, they are likely surrounded by extra-tidal halos and/or tails made up of stars that were tidally stripped from their parent systems. Aims. The stellar surroundings around globular clusters are therefore one of the best places to look for the remnants of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 120 publications
3
42
0
Order By: Relevance
“…This is borne out by observations: Ness et al (2013) found a population of stars in their ARGOS study of the bulge that had properties consistent with NGC 6656, which could be extratidal stars from the cluster. Kunder et al (2014) also found a candidate extratidal star of NGC 6656 in RAVE data.…”
Section: Ngc 6656 (M 22)mentioning
confidence: 78%
“…This is borne out by observations: Ness et al (2013) found a population of stars in their ARGOS study of the bulge that had properties consistent with NGC 6656, which could be extratidal stars from the cluster. Kunder et al (2014) also found a candidate extratidal star of NGC 6656 in RAVE data.…”
Section: Ngc 6656 (M 22)mentioning
confidence: 78%
“…Other six globular clusters have also been associated to the same progenitor, namely: FSR 1758, IC 4499, NGC 3201, 5466, 6101 and 7006. As far as we are aware, 4 of them with previous studies of their external structures have been found to have extra-tidal features : FSR 1758: Barbá et al (2019); NGC 3202: Kunder et al (2014);NGC 5466, and NGC 7006: Jordi & Grebel (2010).…”
Section: Introductionmentioning
confidence: 78%
“…More recently a group of RAVE stars with radial velocities and chemical abundances consistent with stars observed from ω Centauri cluster has been detected by (Kunder et al 2014). As mentioned by Meza et al (2005), the presence of nearby stars with odd kinematics and chemistry, suggests an extra-Galactic origin for them, possibly what they call "tidal relics".…”
Section: Introductionmentioning
confidence: 85%